การพัฒนาผู้เรียนสู่ความเป็นเลิศแบบสาธิตสงขลานครินทร์ - จันทร์ทอง, กนก (วารสารวิทยบริการ มหาวิทยาลัยสงขลานครินทร์ | Academic Services Journal, Prince of Songkla University; Vol 27 No 3 (2559): Academic Services Journal, Prince of Songkla University, 2016)
บทความนี้วิเคราะห์ให้เห็นปัจจัยที่ส่งเสริมให้ผู้เรียนเกิดการเรียนรู้ตามมาตรฐานการเรียนรู้ในระดับดีถึงดีมาก มีความรู้และทักษะเพียงพอ สามารถสอบเข้าเรียนต่อระดับอุดมศึกษาในมหาวิทยาลัยชั้นนำของประเทศ ตัวอย่างความสำเร็จในระดับโรงเรียนในปี พ.ศ. 2557 ได้แก่ นักเรียนชั้นมัธยมศึกษาปีที่ 3 และชั้นมัธยมศึกษาปีที่ 6 มีคะแนนเฉลี่ย O-NET ทุกรายวิชาสูงกว่าค่าเฉลี่ยของประเทศ นักเรียนชั้นมัธยมศึกษาปีที่ 3 มีคะแนนเฉลี่ยสะสมตลอดหลักสูตร 3.00 ขึ้นไป ร้อยละ 86.96 นักเรียนชั้นมัธยมศึกษาปีที่ 6 มีคะแนนเฉลี่ยสะสมตลอดหลักสูตร 3.00 ขึ้นไป ร้อยละ 89.14 นักเรียนทั้งโรงเรียนได้รับวุฒิบัตรเรียนดีเยี่ยม (3.75-4.00) ร้อยละ 57.06 นักเรียนโปรแกรมวิทยาศาสตร์-คณิตศาสตร์สอบได้คณะแพทยศาสตร์ ร้อยละ 20.57 นักเรียนชั้นมัธยมศึกษาตอนต้นได้รับรางวัลพระราชทาน ปีการศึกษา 2557 โรงเรียนได้รับรางวัลพระราชทาน โรงเรียนมัธยมศึกษาขนาดกลาง ปีการศึกษา 2557 ความสำเร็จดังกล่าวเกิดจากปัจจัยสนับสนุน 6 ด้าน ด้วยหลักการบริหารการศึกษาของโรงเรียนสาธิตมหาวิทยาลัยสงขลานครินทร์ ที่เรียกว่า “CREATE” ประกอบด้วย 1) การพัฒนาหลักสูตร (Curriculum Development) 2) การพัฒนาทรัพยากรการเรียนรู้ (Resources for Learning Development) 3) การพัฒนากระบวนการเรียนรู้ (Enhance the Learning Experience) 4) การพัฒนาสิ่งแวดล้อมภายในโรงเรียน (Atmosphere of Learning Development) 5) การพัฒนาอาจารย์ผู้สอน (Teacher Development) และ 6) การพัฒนาระบบการวัดผลและประเมินผล (Evaluation System Development) คำสำคัญ: การบริหารการศึกษา, การจัดการเรียนรู้, การพัฒนาผู้เรียน, การพัฒนาครู   This article on the The Student Development to Excellence by Demonstration School, Prince of Songkla University aimed to identify the suitability of factors to enhance efficient learning of students in accordance with the learning standards at the high and excellent level with their academic abilities and skills to further their studying in our country’s leading universities. Some outstanding achievement of the school in 2014 were the results from O-NET of lower secondary level (Grade 9) students and upper secondary level (Grade12) students in every subject were above national mean, the percentage of both grade 9 students and grade 12 students with grade point average over 3.00 were 86.96 and 89.14 respectively, about 57.06 percent of students had got the certificates of excellent success with grade point average from 3.75 to 4.00, the entrance result o Math-Science students to study in faculty of Medicine was 20.57 percent, a student in grade 9 had got a Royal Award Student of academic year 2014 and the school as well had got a Royal Award for success in management and administration for medium-sized school. All the factors affecting the achievement mentioned above were under the abbreviated word “CREATE” with the six potential educational administration including 1) Curriculum Development 2) Resources for Learning Development 3) Enhance the Learning Experience 4) Atmosphere of Learning Development 5) Teacher Development and 6) Evaluation System Development Keywords: education administration, learning management, the development of learners, teacher development